Activation of Immune and Defense Responses in the Intestinal Mucosa by Outer Membrane Vesicles of Commensal and Probiotic Escherichia coli Strains - Fábrega, María José; Aguilera, Laura; Giménez, Rosa; Varela, Encarna; Alexandra Cañas, María; Antolín, María; Badía, Josefa; Baldomà, Laura (Frontiers in Microbiology, 2016)
The influence of microbiota in human health is well known. Imbalances in microbiome structure have been linked to several diseases. Modulation of microbiota composition through probiotic therapy is an attempt to harness the beneficial effects of commensal microbiota. Although there is wide knowledge of the responses induced by gut microbiota, the microbial factors that mediate these effects are not well known. Gram-negative bacteria release outer membrane vesicles (OMVs) as a secretion mechanism of microbial factors, which have an important role in intercellular communication. Here, we investigated whether OMVs from the probiotic Escherichia coli strain Nissle 1917 or the commensal E. coli strain ECOR12 trigger immune responses in various cellular models: (i) peripheral blood mononuclear cells (PBMCs) as a model of intestinal barrier disruption, (ii) apical stimulation of Caco-2/PMBCs co-culture as a model of intact intestinal mucosa, and (iii) colonic mucosa explants as an ex vivo model. Stimulations with bacterial lysates were also performed. Whereas both OMVs and lysates activated expression and secretion of several cytokines and chemokines in PBMCs, only OMVs induced basolateral secretion and mRNA upregulation of these mediators in the co-culture model. We provide evidence that OMVs are internalized in polarized Caco-2 cells. The activated epithelial cells elicit a response in the underlying immunocompetent cells. The OMVs effects were corroborated in the ex vivo model. This experimental study shows that OMVs are an effective strategy used by beneficial gut bacteria to communicate with and modulate host responses, activating signaling events through the intestinal epithelial barrier.